2020
DOI: 10.30574/wjarr.2020.8.3.0490
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-acute toxicity of the aqueous extract of the stem bark of Rauwolfia vomitoria (Apocynaceae) in Wistar rats.

Abstract: The present study investigated the toxicological potential of the oral administration of the stem bark aqueous extract of R. vomitoria on the liver and kidney in rats. Acute oral toxicity study of the extract to a single dose of 2000 mg/kg was studied in 10 rats of both sexes. Sub –acute oral toxicity of aqueous extract of was carried out on 60 rats. We constituted 4 groups of 10 rats each (5 males and 5 females) which were orally administered 300, 600, and 900 mg/kg of aqueous extract and control group receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several studies have shown that Rauvolfia vomitoria is not toxic when administered orally to Wistar rats, including Bonheur et al 10 work which has shown that this plant, up to a dose of 900 mg/kg of body weight, is not toxic 11 . However, other work and observations, as well as the chemical composition of Rauvolfia vomitoria, point towards a potential toxic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Rauvolfia vomitoria is not toxic when administered orally to Wistar rats, including Bonheur et al 10 work which has shown that this plant, up to a dose of 900 mg/kg of body weight, is not toxic 11 . However, other work and observations, as well as the chemical composition of Rauvolfia vomitoria, point towards a potential toxic risk.…”
Section: Introductionmentioning
confidence: 99%